\(W_2\)-curvature tensor on generalized Sasakian space forms - Venkatesha; B., Shanmukha (CUBO, A Mathematical Journal, 2018)
In this paper, we study W2-pseudosymmetric, W2-locally symmetric, W2-locally Ï†- symmetric and W2-Ï†-recurrent generalized Sasakian space form. Further, illustrative examples are given.